Cryptographic approaches for confidential computations in blockchain. - Morales Escalera, Daniel; Agudo-Ruiz, Isaac (My University, 2023)
Blockchain technologies have been widely re- searched in the last decade, mainly because of the revolution they propose for different use cases. Moving away from centralized solutions that abuse their capabilities, blockchain looks like a great solution for integrity, transparency, and decentral- ization. However, there are still some problems to be solved, lack of privacy being one of the main ones. In this paper, we focus on a subset of the privacy area, which is confidentiality. Although users are increasingly aware of the importance of confidentiality, blockchain poses a barrier to the confidential treatment of data. We initiate the study of cryptographic confidential computing tools and focus on how these technologies can endow the blockchain with better capabilities, i.e., enable rich and versatile applications while pro- tecting users’ data. We identify Zero Knowledge Proofs, Fully Homomorphic Encryption, and Se- cure Multiparty Computation as good candidates to achieve this.
Keywords: Blockchains; Datos - Protección; Blockchain; Privacy; Multi.party computation